Władysław Sommerville Lach-Szyrma and the Cornish Revival - Gmerek, Katarzyna (Wydawnictwo KUL, 2016)
Władysław Sommerville Lach-Szyrma (1841–1915) was born in Devonport, 25 December 1841, to a Polish father and English mother. As an Anglican clergyman, writer and historian he contributed to the Cornish Revival in the early twentieth century, with his historical, folklorist and linguistic research. In Poland he is relatively unknown, unlike his more famous father – the academic and writer Krystyn Lach-Szyrma. This paper examines his Polish background, and the Cornish chapter in his life, starting from his gathering of Cornish folklore and ending with his cooperation with Henry Jenner on the rebirth of the language. It would be difficult to understand his interests in languages and cultures without discussing his Polish background.
Keywords: Władysław Sommerville Lach-Szyrma; Cornish Revival; Cornish language; Henry Jenner; Celtic studies